Undertaking to care and to protect : The experience of killing healthy homeless animals in South Africa - Van Zyl, Henriette Louise (Rhodes University, Faculty of Humanities, Department of Psychology, 2014)
Although animal welfare workers overwhelmingly describe themselves as animal lovers the exigencies of day to day animal welfare work often require that they perform euthanasia of healthy animals as part of welfare shelter management, and animal population control. In this research study, the particular burdens placed upon seven South Animal welfare workers who are required to rescue, care for, nurture and rehabilitate the animals in their care; while simultaneously being required to kill these same "“ often physically and behaviourally healthy - animals after a specific period of time, or in response to various logistical, procedural and practical intricacies, ranging from lack of space and resources to an unavailability of suitable homes; are explored from an interpretative phenomenological approach using the Interpretative Phenomenological Method (IPA), and from a South African perspective. It was found that animal-loving individuals engaged in the care and subsequent euthanasia of healthy animals report experiencing profound personal, interpersonal and professional and ideological (dis)stress related to guilt, sorrow, moral unease and horror. Four themes emerged from interview data, which are discussed in relation to relevant research and literature. Experiences in a South African context were found to be very much aligned with those reported in previous research and literature pertaining to this topic. In particular, it was found that there is a need to articulate specifically, and precisely the nature of the act. It is proposed that the term "Agapéthanasia" would be appropriate and useful in this field.
Keywords: Animal welfare -- Moral and ethical aspects -- South Africa; Euthanasia of animals -- South Africa; Euthanasia of animals -- Psychological aspects; Human-animal relationships -- South Africa; Animal rights -- South Africa